KERAGAMAN ARTHROPODA MUSUH ALAMI PADA FASE VEGETATIF VARIETAS PADI PERSILANGAN DAN MUTAN: Arthropoda musuh alami, Keragaman, Varietas padi, Vegetatif - Alu, Muhammad Tholut; Rahmiyah, Muzayyanah; Heru Praptana, Raden (Universitas Islam Malang, 2025)
Increasing rice productivity requires not only the utilization of high-yielding varieties, but also ecologically friendly insect control. The use of natural enemy arthropods as biological control agents is critical for long-term pest suppression. The purpose of this study was to identify the types of natural enemy arthropods and examine the diversity (H'), evenness (E), and dominance (D) indices of many rice varieties during the vegetative phase, including hybrid varieties (Mantap, INPARI 32, and IPB 3S) and mutant varieties (Srinuk and Gamagora 7). This research was conducted using an exploratory method at the Agricultural Training Center of Central Java Province from January to March 2025. Data collection was carried out using sweep nets and direct observations at 2, 4, 6, and 8 weeks after transplanting (WAT), followed by arthropod identification at the Laboratory of Universitas Tidar. The results showed the presence of nine species of predatory arthropods, namely Paederus fuscipes, Menochilus sexmaculatus, Conocephalus longipennis, Orthetrum sabina, Agriocnemis femina, Cyrtorhinus lividipennis, Solenopsis geminata, Tetragnatha javana, and Oxyopes javanus. Diversity, evenness, and dominance indices differed between rice types, with mutant variants generally having greater diversity values. The diversity of natural enemy arthropods suggests that they may play an important role in implementing more effective and environmentally friendly Integrated Pest Management strategies. Keywords: Diversity, Natural enemy arthropods, Rice varieties, Vegetative phase